MORFOLOGI CERITA ANAK SERATUS SATU - Sri Yono NFN (Balai Bahasa Provinsi Papua, 2019)
The people of Sarmi has varieties of oral literature that scatter among the big five tribes (Sobei, Armati, Rumbuai, Manirem, and Isirawa). The main data of this research is Anak Seratus Satu folktale from Sobei Tribe. This descriptive qualitative research aims to document oral literature and to analyze the morphology of Sobei folktale based on Vladimir Propp’s structure. From the analysis, it is known that Sobei folktale is relatively complete though the plot is quite simple. There are twenty two functions and five spheres of action in it. Basically, the introduction of the character was functionally as awhole because it connected to the main function of story. Briefly, this folktale reflected the competitive manner of Sobei people.